2009
DOI: 10.1007/s00299-009-0790-3
|View full text |Cite|
|
Sign up to set email alerts
|

Green-tissue-specific, C4-PEPC-promoter-driven expression of Cry1Ab makes transgenic potato plants resistant to tuber moth (Phthorimaea operculella, Zeller)

Abstract: An important strategy for obtaining a safer transgenic plant may be the use of a spatial- or tissue-specific promoter, instead of a constitutive one. In this study, we have used a light-inducible maize PEPC promoter to regulate the cry1Ab gene, aiming to produce transgenic potatoes that are resistant to potato tuber moth (PTM) (Phthorimaea operculella, Zeller). Out of 60 regenerated lines having normal phenotypes, 55 lines were PCR-positive for both the cry1Ab and nptII genes. Southern analysis on three select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…However, the constitutive expression of transgenes using constitutive promoters-e.g., cauliflower mosaic virus (CaMV) 35S-is widely used in plant genetic engineering, but this may impose an extra metabolic burden and other metabolic effects on transgenic plants [17]. For this reason, we used a light inducible promoter (PEPC) for the Cry1Ab expression in transgenic potatoes [15]. The light-inducible PEPC promoter has specific advantages in plant genetic engineering for green tissue-consuming pests [15].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the constitutive expression of transgenes using constitutive promoters-e.g., cauliflower mosaic virus (CaMV) 35S-is widely used in plant genetic engineering, but this may impose an extra metabolic burden and other metabolic effects on transgenic plants [17]. For this reason, we used a light inducible promoter (PEPC) for the Cry1Ab expression in transgenic potatoes [15]. The light-inducible PEPC promoter has specific advantages in plant genetic engineering for green tissue-consuming pests [15].…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, we used a light inducible promoter (PEPC) for the Cry1Ab expression in transgenic potatoes [15]. The light-inducible PEPC promoter has specific advantages in plant genetic engineering for green tissue-consuming pests [15]. The application of the PEPC promoter would not only reduce the metabolic pressure imposed on transgenic potato plants, but also reduce concerns over the food safety of transgenic plants [17,18].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A transgenic potato resistant to potato tuber moths with 100% tuber moth larval mortality was developed by expressing cry1Ab under the control of the PEPC promoter, a green tissue-specific and light-inducible promoter from maize [ 39 ]. Cry9C driven by PNZIP promoter, a green tissue promoter from Pharbitis nil , was used to develop transgenic pest-resistant cotton, and the accumulation of cry9C protein in seeds was 100 times lower than that observed for the seeds of the CaMV 35S:Cry9C line [ 40 ]. In our study, we have isolated a novel rice green tissue-specific promoter that does not drive expression in endosperm, and the GUS activity in seeds was much lower than in green tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenic potato plants harbouring cry1Ab gene for potato tuber moth (Phthorimaea operculella (Zeller)) resistance have been developed in the Agricultural Biotechnology Research Institute of Iran (Ghasimi Hagh et al, 2009). After field trials, the possible use of this transgenic potato as food and feed will be reported.…”
Section: Introductionmentioning
confidence: 99%